Predicting multiple sclerosis following isolated optic neuritis in children. Issue 9 (12th May 2013) - Heussinger, N.; Kontopantelis, E.; Rompel, O.; Paulides, M.; Trollmann, R.
Abstract : Background and purpose: Isolated optic neuritis (ON) is frequently the initial symptom of multiple sclerosis (MS). The aim of our study was to investigate the risk of conversion to MS in children following isolated ON and to evaluate the performance of current diagnostic methods such as cranial magnetic resonance imaging (cMRI), visual evoked potentials (VEPs) and oligoclonal bands in spinal fluid (OCB) as predictive factors for MS development. Methods: Medical records of 159 patients presenting with acute ON between 2000 and 2010 at the Department of Pediatrics, University of Erlangen, were screened; 34 patients with isolated ON were identified. Progression to MS was defined according to the revised McDonald criteria 2005. Age, sex, VEPs, ON type, cMRI, OCB and visual recovery were assessed as predictors of progression to MS using simple logistic regressions. A multiple logistic regression model included variables found to be significant in univariate analyses. Results: Abnormal cMRI was associated with an increase in the odds of MS development (odds ratio 20.57; 95% CI 2.16–196.10, P  < 0.001), as was positive OCB (odds ratio 12.0; 95% CI 1.29–111.32, P  = 0.001). However, only cMRI remained statistically significant in multiple regressions. Conclusions: Multiple sclerosis‐like cMRI lesions and OCB are suitable for assessing the risk of progression to MS following isolated ON, as children with both cMRI abnormalities and positive OCB at onset of ON are at high risk of developing MS.